Expression of Livin and the Inhibition of Tumor Progression by Livin Silencing in Laryngohyopharyngeal Cancer. (2nd September 2014) - Yoon, Tae Mi; Cho, Wan Seok; Lee, Jae Hun; Lee, Dong Hoon; Lee, Joon Kyoo; Lim, Sang Chul
Abstract : Objectives: Livin, a member of the inhibitors of apoptosis protein family, is expressed in various cancers and is associated with tumor progression. However, there is no report about the significance of Livin in laryngohypopharyngeal sqaumous cell carcinoma (LHSCC). In this study, we evaluated the expression of Livin in human LHSCC and investigated whether Livin knockdown using small interfering‐RNA (siRNA) affects tumor aggressiveness in LHSCC cells. Methods: Livin expression in human LHSCC tissues was detected by immunohistochemistry. The relationships between Livin expression and clinicopathologic variables were analyzed. Livin specific siRNA was used to silence the endogenous Livin gene expression in SNU1041 and PCI1 human LHSCC cell lines. Cell invasion, cell migration, and cell apoptosis assays were performed to assess the impact of Livin on cancer cell behavior in human LHSCC cells. Results: High immunoreactivity of Livin was observed in 22 (36.7%) of the 60 LHSCC tissues relative to adjacent normal mucosa. In the positive Livin expression group, distant metastasis tended to occur frequently, but the difference was not statistically significant ( P =. 06). Livin knockdown by siRNA induced cell apoptosis through activation of caspase 3, caspase 7, and poly ADP ribose polymerase in LHSCC cells. Livin knockdown also resulted in significantly reduced cell invasion and migration in LHSCC cells. Conclusions: These results suggest that Livin silencing mediated siRNA may be associated with the reversal of invasive capacity in LHSCC.